Logiques au cœur des choix de l’école secondaire par des parents immigrants résidant à Montréal - Grenier, Véronique (Canadian Journal of Education/Revue canadienne de l’éducation, 2022)
This article aims to better understand the motives for immigrant parents’ choices of a high school for their children in Montreal. Mobilizing Dubet’ sociology of experience (1994), the analysis reveals that immigrant parents try to articulate distinct logics, sometimes in contradiction, in order to make their decision. By articulating the effects of social class, ethnocultural/racial belonging, but also immigrant parents’ specific relationship with the host society and its institutions on the motives for choosing a school, the article contributes to the advancement of knowledge on this matter. First, the analysis reveals the (ir)relevance of social class as an analytical category of immigrant parents’ motives of choice. Then, it sheds light on specific reasons linked to the relocation that accompanies immigration, which are rarely mentioned in the literature on school choice. Finally, it corroborates the issues experienced by racialized immigrant parents raised by other studies.